The rule of admissibility of evidence in the criminal process of continental Europe - Jerzy Skorupka (Revista Brasileira de Direito Processual Penal, 2021)
This paper presents a doctrinal review of the rule of admissibility of evidence in the criminal process of continental Europe, which can be understood narrowly as applying exclusively to the question of acceptability, i.e. determination what evidence can be admitted. This rule can also be understood in broad terms and applied to determine not only the admissibility of evidence but also its relevance and adequacy. Much attention was paid to the functions performed by the admissibility rule, especially its guarantee function. The state of scientific discussion on the recognition of unlawfully obtained evidence as “inadmissible evidence”, and the author’s views on this issue were also presented.